Peran Kolaborasi Kanwil DJP Jatim I dan Forum Tax Center Surabaya dalam Meningkatkan Kepatuhan Pajak UMKM melalui Business Development Service (BDS) - Yoga Adi Prayogi; Adhityawati Kusumawardhani; Rifda Fitrianty; Ratna Anggraini Aripratiwi; Norbertus Purnomolastu; Dian Anita Nuswantara (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
The Regional Office of DJP East Java I and the Surabaya Tax Center Forum are working together to run the Business Development Services (BDS) program. The goal is to get micro, small, and medium enterprises (MSMEs) to pay their taxes more accurately and help them do better in business. The program involved 21 MSMEs selected based on their possession of a Taxpayer Identification Number (NPWP) and Business Identification Number (NIB). The implementation methods included tax education, digital marketing training, and business financing solutions using a participatory approach, lectures, discussions, and interactive simulations. Evaluation was conducted through questionnaires to assess participants’ understanding of the materials presented and the program’s impact on their business capabilities. The results showed a 35% increase in participants’ understanding scores, with the majority of respondents indicating that the program was relevant and beneficial. This program also successfully increased tax awareness, digital marketing skills, and understanding of inclusive financing access. These results show that other areas can use the same collaborative and locally tailored method to help small and medium-sized businesses change their economies.